Cost-effectiveness analysis of durvalumab plus chemotherapy as first-line treatment for biliary tract cancer - Ye, Zhuo-miao; Xu, Zhe; Li, Huan; Li, Qian (Frontiers in Public Health, 2023)
Abstract: Objective: The TOPAZ-1 trial reported a significant survival benefit of durvalumab in combination with chemotherapy for the first-line treatment of biliary tract cancer (BTC). However, no studies have evaluated the economics of this treatment option. The aim of this study was to assess the cost effectiveness of durvalumab in combination with chemotherapy compared to placebo plus chemotherapy from the perspective of US and Chinese payers. Methods: Based on clinical data from the TOPAZ-1 trial, a markov model was developed to simulate 10-year life expectancy and total healthcare costs for patients with BTC. The treatment group received durvalumab in combination with chemotherapy and the control group received placebo plus chemotherapy. The primary outcomes analysed included quality-adjusted life years (QALYs) and incremental cost-effectiveness ratios (ICERs). Uncertainty in the analysis results was assessed by sensitivity analysis. Results: For US payers, the placebo plus chemotherapy group had a total cost of 57,568.59 and a utility of 1.14 QALYs, while the durvalumab plus chemotherapy group had a total cost of 217,020.46, a utility of 1.52 QALYs and an ICER of 426,301.52/QALY. For Chinese payers, the ICER of durvalumab plus chemotherapy group was 410227.52/ QALY. Sensitivity analysis showed that the analysis was most sensitive to the price of durvalumab. For US and Chinese payers, under the respective WTP thresholds, the likelihood of the durvalumab combination chemotherapy arm being cost-effective was 0%. Conclusions: Both in China and in the US, durvalumab in combination with chemotherapy is not a cost-effective option for the first-line treatment of BTC compared with chemotherapy. Keywords: cost effectiveness analysis; durvalumab; biliary tract cancer; markov model Key points: Our study provided the first assessment of the cost-effectiveness of durvalumab plus chemotherapy for the first-line treatment of advanced biliary tract cancer and showed that the regimen was not cost-effective for both U.S. and Chinese payers. Further price reductions for durvalumab were needed.